2014
DOI: 10.3174/ajnr.a4027
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Sacroplasty: A Large Single-Center Experience

Abstract: BACKGROUND AND PURPOSE:Sacral insufficiency fractures are a common cause of severe low back pain and immobilization in patients with osteoporosis or cancer. Current practice guideline recommendations range from analgesia and physical therapy to resection with surgical fixation. We sought to assess the safety and effectiveness of sacroplasty, an emerging minimally invasive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 19 publications
0
30
0
1
Order By: Relevance
“…In 2012, a review on the only five studies with at least 10 patients available concluded that sacroplasty was a well tolerated procedure; although asymptomatic linkage may occur, it was still potentially effective for treating the pain and disability; none of them was randomized vs. conservative management [29]. In 2014, the same team confirmed in a retrospective study on 53 patients the effectiveness on pain relief and increased mobility and the safety of sacroplasty, as well as other authors on a limited group of patients [30][31][32] 14). In a series of 20 patients still painful and disabled after 3 weeks of conservative treatment, sacroplasty using highly viscous cement activated by radiofrequency led to a significant decrease of pain at day 2 (8.8 AE 1.1 vs. 2.3 AE 0.7; P < 0.001), stable after 6 and 12 months and all patients could be fully remobilized and discharged back home; no cement linkage was observed [33 & ].…”
Section: Treatmentmentioning
confidence: 85%
“…In 2012, a review on the only five studies with at least 10 patients available concluded that sacroplasty was a well tolerated procedure; although asymptomatic linkage may occur, it was still potentially effective for treating the pain and disability; none of them was randomized vs. conservative management [29]. In 2014, the same team confirmed in a retrospective study on 53 patients the effectiveness on pain relief and increased mobility and the safety of sacroplasty, as well as other authors on a limited group of patients [30][31][32] 14). In a series of 20 patients still painful and disabled after 3 weeks of conservative treatment, sacroplasty using highly viscous cement activated by radiofrequency led to a significant decrease of pain at day 2 (8.8 AE 1.1 vs. 2.3 AE 0.7; P < 0.001), stable after 6 and 12 months and all patients could be fully remobilized and discharged back home; no cement linkage was observed [33 & ].…”
Section: Treatmentmentioning
confidence: 85%
“…Direct injection of polymethylmethacrylate into bone marrow edema lesions associated with vertebral compression fractures or sacral insufficiency fractures have been performed more frequently [10,28]. However, to our knowledge, the Subchondroplasty 1 procedure is the first to use direct injection of calcium phosphate into bone marrow edema lesions associated with knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…Plusieurs autres régions du bassin peuvent également bénéficier de la cimentoplastie dans le cadre de lésions secondaires hyperalgiques [17]. Parmi ces localisations, on retiendra principalement l'aile iliaque ainsi que les branches ilio-et ischiopubiennes [18].…”
Section: Plasties Cotyloïdiennes (Cotyloplasties) Et Plasties Du Bassinunclassified